Exploring social presence transfer in real-virtual human interaction - Daher, Salam; Kangsoo Kim; Myungho Lee; Raij, Andrew; Schubert, Ryan; Bailenson, Jeremy; Welch, Greg (Proceedings of the Workshop on Future Trends of Distributed Computing Systems, 2016)
We explore whether a peripheral observation of apparent mutual social presence between a real human (RH) and a virtual human (VH) can in turn increase a subject's sense of social presence with the VH. In other words, we explore whether social presence can "transfer" from one RH-VH interaction to another. Specifically, we carried out an experiment where human subjects were asked to play a game with a VH. As they entered the game room, approximately half of the subjects were exposed to a brief but apparently engaging conversation between an RH and the VH. The subjects who were exposed to the brief RH-VH interaction had significantly higher measures of both emotional connection and the attentional allocation dimension of social presence for the VH, compared to those who were not. We describe the motivation, the experiment, and the results.